SERVICE CYNOLOGY IN THE MODERN SECURITY SYSTEM: BIO-SENSORS AND STRATEGIC OPPORTUNITIES (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the role of service cynology within modern military and law enforcement systems. Despite rapid technological advancements, the biological sensing capabilities of service dogs and their role in decision-making under extreme conditions are examined as a "moral-biological force multiplier." The study provides a scientific justification for the effectiveness of cynology units in counter-terrorism, border protection, and search-and-rescue (SAR) operations.
Keywords: Service cynology, K9 units, bio-sensor, operational effectiveness, olfactory properties, counter-terrorism, border protection.